2018
DOI: 10.1017/s0033291718003136
|View full text |Cite
|
Sign up to set email alerts
|

Frontostriatal functional connectivity correlates with repetitive behaviour across autism spectrum disorder and obsessive–compulsive disorder

Abstract: BackgroundAutism spectrum disorder (ASD) and obsessive–compulsive disorder (OCD) are neurodevelopmental disorders with considerable overlap in terms of their defining symptoms of compulsivity/repetitive behaviour. Little is known about the extent to which ASD and OCD have common versus distinct neural correlates of compulsivity. Previous research points to potentially common dysfunction in frontostriatal connectivity, but direct comparisons in one study are lacking. Here, we assessed frontostriatal resting-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Notably, a strong difference was found between the data-driven clusters (i.e., site effects), but not between the diagnostic groups, supporting the discrepancy between the behaviourally based diagnoses and the underling neurobiological presentation ( Easson et al, 2019 ). Another recent report also found that the overall connectivity patterns were very similar amongst those with ASD, ADHD, schizophrenia and even TDs ( Spronk et al, 2018 ), while a third study, assessed frontostriatal rs-fc in children with ASD and OCD, and found no diagnosis-specific differences but an association between increased nucleus accumbens connectivity with the frontal region and symptom severity in repetitive behaviours ( Akkermans et al, 2018 ). Our findings and those of the recent literature suggest that a categorical approach may not be useful even to define typically developing controls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, a strong difference was found between the data-driven clusters (i.e., site effects), but not between the diagnostic groups, supporting the discrepancy between the behaviourally based diagnoses and the underling neurobiological presentation ( Easson et al, 2019 ). Another recent report also found that the overall connectivity patterns were very similar amongst those with ASD, ADHD, schizophrenia and even TDs ( Spronk et al, 2018 ), while a third study, assessed frontostriatal rs-fc in children with ASD and OCD, and found no diagnosis-specific differences but an association between increased nucleus accumbens connectivity with the frontal region and symptom severity in repetitive behaviours ( Akkermans et al, 2018 ). Our findings and those of the recent literature suggest that a categorical approach may not be useful even to define typically developing controls.…”
Section: Discussionmentioning
confidence: 97%
“…Recent investigations tackling this question have demonstrated the value of measuring resting-state functional connectivity (rs-fc), which allows the study of intrinsic large-scale brain networks that underlie a range of sensory and cognitive processes. Although emerging evidence from genetic studies support shared genetic susceptibility across NDD groups ( Lionel et al, 2014 , Martin et al, 2014 , Zarrei et al, 2019 ), studies of rs-fc have remained largely inconsistent, in findings both in independent analyses of each NDD ( Castellanos and Aoki, 2016 , Gürsel et al, 2018a , Hull et al, 2017 ) and in direct comparisons between NDDs ( Akkermans et al, 2018 , Dajani et al, 2019 , Di Martino et al, 2013 , Jung et al, 2019 , Ray et al, 2014 ). Most studies have relied on case-control designs using diagnostic labels for comparisons, but have not explored heterogeneity within and across the groups.…”
Section: Introductionmentioning
confidence: 99%
“…Flexibility deficits in OCD manifest themselves as maladaptive patterns of recurrent and persistent thoughts, urges and impulses that are intrusive, as well as compulsions, including repetitive behaviours that an individual feels driven to perform 69 . Neuroimaging investigations across OCD and ASD provide evidence that increased functional connectivity within frontostriatal circuitry relates to more severe symptoms of repetitive behaviour 91 . In OCD, reduced activation of the OFC and frontostriatal regions during cognitive flexibility task performance is regularly reported 92,93 .…”
Section: Flexibility In Adolescence and Midlifementioning
confidence: 99%
“…Notably, in mice, increases in white matter were seen following GE CAPs exposures, whereas postnatal exposures markedly reduced white matter. 63,64 Nucleus accumbens dysfunction in ASD has been related to social and repetitive behavior deficits and response inhibition 95,96,103,104,96 and to altered self-control in ADHD. 105,106 While ASD etiology remains unknown, inflammation is considered key, and biomarkers include altered trans-sulfuration pathways and increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%